Reflecting on Ethical Processes and Dilemmas in Doctoral Research - Aimee Quickfall (MDPI AG, 2022)
This paper discusses ethical dilemmas from an early-career researcher perspective, drawing upon doctoral research experiences-my own. The doctoral study involved life-history interviews with five primary-school-teacher mothers. During the study, ethical dilemmas arose that were not considered by me or in the official university ethical processes. This left me feeling vulnerable in the data-collection period and overwhelmed with concerns for the well-being of participants and for myself as researcher. This paper draws on my journal entries and reflections; detailed reflections of the pre-, during and post-fieldwork stages were collected (totalling over 600 entries). The paper utilizes critical incidents analysis to explore two ethical dilemmas from the data collection phase. Findings include personal reflections on experiences of university processes and the mismatch between the metaphor of ethics as a 'hurdle' on a smooth track to completion, and the real-life incidents and dilemmas that followed ethical approval. Recommendations are made for a consideration of doctoral ethical dilemma support and the limitations of formal ethics processes in UK universities.